Перша в Україні знахідка гриба Skeletocutis nemaralis A. Korhonen & Miettinen з Національного природного парку «Мезинський» - Ачкасов, Данило Олександрович (Львів : ТОВ «Ромус-поліграф», 2021)
Based on the study of micromorphology and nucleotide sequence of the ITS region rDNA, the specimen CWU Myc AB 774 from the Chernihiv region was identified by us as Skeletocutis nemoralis A. Korhonen & Miettinen.
The first in Ukraine find of Skeletocutis nemoralis A. Korhonen & Miettinen from the National Nature Park “Mezynskyi”
Keywords: гриби; біорізноманіття; трутовики; Національний природний парк; Чернігівська область; Україна